基于接近度修改设备之间的交互类型的方法、系统 (2024)
一般而言，本公开中描述的主题可以体现在用于基于接近度来修改移动设备与外围设备之间的交互的方法、设备和程序产品中。移动设备监视无线通信信道，并且通过该信道从外围设备接收指示移动设备位于与外围设备的第一接近地带内的传输。移动设备确定设备之间的距离值。当移动设备确定距离值满足阈值时，移动设备视觉地指示其在与外围设备的第二接近地带内。由于移动设备使用第二通信协议从外围设备接收数据，移动设备确定其位于与外围设备的第三接近地带内，并且执行动作。 In general, the subject matter described in this disclosure can be embodied in methods, devices, and program products for modifying interactions between a mobile device and a peripheral device based on proximity. The mobile device monitors a wireless communication channel and receives a transmission from the peripheral device over the channel indicating that the mobile device is located within a first zone of proximity to the peripheral device. The mobile device determines distance values between the devices. When the mobile device determines that a distance value satisfies a threshold value, the mobile device visually indicates that it is within a second zone of proximity to the peripheral device. As a result of the mobile device receiving data from the peripheral device using a second communi